Deterministic networks using segment routing - Simeonova, Tsvetelina (Yearbook Telecommunications, 2024)
The aim of the work is to analyze the new direction in telecommunications - creation of deterministic networks using segment routing technology within IPv6. The results obtained cover the consideration of network functions in a deterministic IP network (DIP), its architecture and principle of operation. The various aspects of segment routing (SR) technology are given, as well as the many use cases, incl. traffic engineering, network failure recovery, stateless chaining of services, introduction of 5G network "slices", cross-domain switching to connect users to applications on servers in multiple data centers, segment routing in SD-WAN. The main technologies of a DIP network are considered: traffic flow shaping (smoothing), input scheduling, time slot scheduling. The contributions relate to analysis and conclusions on the applicability, scope and development of DIP networks using segment routing technology within IPv6.